Fluctuations in the values of the activity parameters of micron iron powder after microwave irradiation - Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich; Chumerin P. Yu. Pavel Yurievich; Kalinich I. Ivan; Tsybanev A. S. Aleksandr Sergeevich; Gubarev F. A. Fedor Aleksandrovich (2017, 2017)
Title screen